CASE REPORT OF EPSTEIN-BARR VIRUS-INDUCED AUTOIMMUNE VITILIGO IN NIGERIA - Michael Akolawole; Oluwasola Ayosanmi; Olanrewaju Adeniran; Ifeanyichukwu Onuoha; Osaho Omoregie; Esosa Omoregie (European Medical Journal, 2022)
Vitiligo is an acquired skin depigmenting disorder resulting from melanocytes loss in the epidermis, associated with an autoimmune aetiopathophysiology. However, there are limited data about the association between vitiligo and Epstein-Barr virus (EBV). Hence, the authors present a case of a 43-year-old male who had progressive symmetrical hypopigmented macules, sometimes coalescing to patches that were generalised but predominantly on the face and torso, with scanty involvement of proximal and distal extremities of the body. The diagnosis of vitiligo was made clinically, and seborrhoeic dermatitis was considered as a differential. Since the patient had been offered treatment for seborrhoeic dermatitis using antifungal with no relief and extensive depigmentation, the authors' working diagnosis was vitiligo and was confirmed with histology. To establish the likely cause of the condition, viral serology for HIV, Cytomegalovirus, herpes, and EBV were completed, but only EBV serology was abnormal. Therefore, the authors report this case to encourage clinicians to consider EBV infection in the aetiology and predisposition for vitiligo to help explore other pathology that the virus may cause.